Fisetin Exerts Antioxidant and Neuroprotective Effects in Multiple Mutant hSOD1 Models of Amyotrophic Lateral Sclerosis by Activating ERK. (21st May 2018) - Wang, T.H.; Wang, S.Y.; Wang, X.D.; Jiang, H.Q.; Yang, Y.Q.; Wang, Y.; Cheng, J.L.; Zhang, C.T.; Liang, W.W.; Feng, H.L.
Graphical abstract: Fisetin exerts protective and antioxidant effects on MNs by activating ERK. Fisetin activates the MEK–ERK signaling pathway and subsequently increases the expression of genes involved in the antioxidant response, such as HO-1, GPx, and catalase, which enhance the antioxidant defense mechanisms and inhibit oxidative stress. In addition, mutant detergent-insoluble hSOD1 proteins are also scavenged by fisetin to protect cells from ROS-induced damage. Highlights: Fisetin treatment exerts beneficial effects on mutant hSOD1 ALS models. Fisetin decreases free radical levels to protect against oxidative stress. Fisetin upregulates the expression of antioxidant factors by activating ERK. Fisetin scavenges hSOD1 levels, especially the detergent-insoluble mutant hSOD1 proteins. Abstract: Oxidative stress exhibits a central role in the course of amyotrophic lateral sclerosis (ALS), a progressive neurodegenerative disease commonly found to include a copper/zinc superoxide dismutase (SOD1) gene mutation. Fisetin, a natural antioxidant, has shown benefits in varied neurodegenerative diseases. The possible effect of fisetin in ALS has not been clarified as of yet. We investigated whether fisetin affected mutant hSOD1 ALS models. Three different hSOD1-related mutant models were used: Drosophila expressing mutant hSOD1 G85R, hSOD1 G93A NSC34 cells, and transgenic mice. Fisetin treatment provided neuroprotection as demonstrated by an improved survival rate, attenuated motor impairment, reduced ROS damage and regulated redox homeostasis compared with those in controls. Furthermore, fisetin increased the expression of phosphorylated ERK and upregulated antioxidant factors, which were reversed by MEK/ERK inhibition. Finally, fisetin reduced the levels of both mutant and wild-type hSOD1 in vivo and in vitro, as well as the levels of detergent-insoluble hSOD1 proteins. The results indicate that fisetin protects cells from ROS damage and improves the pathological behaviors caused by oxidative stress in disease models related to SOD1 gene mutations probably by activating ERK, thereby providing a potential treatment for ALS.